Evaluation of free radical damage to myocardial membranes in ischaemia and reperfusion - Coetzee, Isabella H. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med.Biochem.)) -- University of Stellenbosch, 1990.